Konsepsi Otonomi Daerah Dalam Pola Relasi Mandala Kedatuan Sriwijaya - Trinanda, Ghea Anissah (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The Srivijaya Kingdom, in its historical journey, showed a strong commitment to giving more independence to the regions under its control. This meant that these regions could manage their own local matters, taking into account their unique characteristics. This idea played a vital role in boosting the economy and stability of the entire kingdom, making the